(untitled) (Acta Scientiarum. Health Sciences, 2013)
The social and economic profile of alcohol-traumatized young people and alcohol users is provided through an exploratory and transversal analysis with 10-24-year-old young people attended to at the Emergency Section of a hospital in the western region of the state of Paraná, Brazil. Data were processed by Statistica 8.0. One hundred and twelve young people were classified in three groups according to alcohol intake: trauma associated with alcoholic beverage consumption; alcohol consumers without any alcohol intake during the previous six hours; teetotalers. Alcohol trauma was predominant in male young people with complete primary schooling, family income between R 901 and R 1500, without any personal income and working regularly. Higher occurrence lay within the 15-20 years age bracket regardless of their alcohol intake pattern. Results show that young people’s social and economical profile affects the capacity of people in acknowledging and managing the dangers to which they are exposed. Interventions are relevant when the historical and social contexts are taken into account so that changes in health, disease and care processes could be enhanced.